Peningkatan Daya Saing Bisnis melalui Technopreneurship - Yuliana Yuliana (Penerbit Goodwood, 2021)
Purpose: To describe how the increase of competitiveness in business through technopreneurship Methodology: This is a narrative literature review. Literature was taken from Science Direct and Google Scholar databases. Keywords were business, competitiveness, increase, technopreneurship Results: Results revealed that technopreneurship is important in increasing the competitiveness in business, especially in digital era. Technopreneurship in information technology is successful in all over the world. All nations appreciate the presence of an advanced information and communication technology as a tool for increasing the process in private and government sectors. This condition will make the citizens easier in doing daily activities. The innovation in technology also open new opportunities and challenges for the development of the nations. Therefore, it can be inferred that information technology is an important part in business because it helps the development process in the business Limitations: This paper is a narrative literature review. There are only few studies about the competitiveness in business through technopreneurship. Further studies are needed for the strategy in increasing the competitiveness in business through technopreneurship. Contribution: The contribution of this paper is for the increasing of competitiveness through technopreneurship which is very essential during the digital era.